2020
DOI: 10.1016/j.apnu.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Covid-19 pandemic on mental health among Albanian people residing in the country and abroad – Implications for mental care

Abstract: Background: Coronavirus disease caused by the novel coronavirus Covid-19 is a current worldwide outbreak. The use of quarantine and isolation proved effective in containing the spread of infection. Objectives: The purpose of this cross-sectional study was to assess the mental health of Albanian people residing in the country and abroad during the quarantine period for the Covid-19 pandemic. Design: This study was carried out from 25th March-20th April 2020 through a web survey shared on social networks. The go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…However, studies in Albania have reported a high prevalence of mental health issues during the quarantine period. 23,41 Decrease of infection diseases events has been also reported in other studies. 10 This decrease is mainly due to the lockdown and the restriction measures.…”
Section: Discussionsupporting
confidence: 79%
“…However, studies in Albania have reported a high prevalence of mental health issues during the quarantine period. 23,41 Decrease of infection diseases events has been also reported in other studies. 10 This decrease is mainly due to the lockdown and the restriction measures.…”
Section: Discussionsupporting
confidence: 79%
“…A high prevalence of stress and post-traumatic stress disorders was documented among Nepalese 150 , Lebanese 151 , Saudi Arabian 152 , Vietnamese 153 , and Philippine nationals 154 at the height of lockdown. High levels of anxiety and depression were also documented in studies from India [155][156][157] , Ecuador 158 , Albania 159 , Ireland 160 , Hungary 88,161 , Spain 162 , Palestine 163 , the UK 164 , Kuwait 165 , Brazil, and Portugal 166 . The prevalence of people reporting clinical depression and anxiety in a sample of 1215 respondents in Italy was recorded to be 32.3% and 35.7%, respectively (compared to 15.39% and 21.40%, respectively, during pre-COVID-19 times) 142 .…”
Section: Stressmentioning
confidence: 81%
“… 30 In addition, being a health care worker increases the levels of anxiety and psychological distress in comparison to the general population whose mental health has been affected by the pandemic even though they are not in direct contact with COVID-19 patients. 32 , 33 A study found that the lack of mental health support in the workplace is statistically related to moderate levels of anxiety among all health care workers. Anxiety is highest among the young, the age group 41–60 years old, male and married health care workers.…”
Section: Discussionmentioning
confidence: 99%